Socialization of filling in SINTA data: Improving lecturers' research and publication track records - H. Hardani; Reny Amalia Permata; S. Syaidatussalihah; Alpiana Hidayatulloh; Dwi Monika Ningrum; Alpi Zaidah (Universitas Muhammadiyah Malang, 2025)
The SINTA (Science and Technology Index) National Indexation System is a platform developed by the Indonesian Ministry of Education, Culture, Research, and Technology to support the management of research data, publications, and community service by lecturers and researchers. However, the lack of understanding regarding how to fill in SINTA data is often an obstacle in improving research and publication track records. This community service activity aims to provide socialization and training to lecturers regarding SINTA data filling following applicable guidelines. The methods used include presentation sessions, simulations, and direct assistance as well as giving pre-test and post-tests to participants. The results of the activity showed that participants experienced an increase in understanding and skills in filling SINTA data by 86%, which had implications for increasing the visibility and academic track record of lecturers. This activity is expected to contribute to improving the quality of research and scientific publications in Indonesia